The functionalization of polyacrylamide with MoS2 nanoflakes for use in transient photodetectors. Issue 5 (10th February 2021) - Verma, Arpit; Chaudhary, Priyanka; Tripathi, Ravi Kant; Yadav, B. C.
Abstract : Herein, we report solvent-free frontal polymerization of acrylamide monomers with transitional metal dichalcogenides (TMDs), i.e. MoS2 nanoflakes. Abstract : Herein, we report solvent-free frontal polymerization of acrylamide monomers with transition metal dichalcogenides (TMDs), i.e. MoS2 nanoflakes. Scanning electron microscopic (SEM) images confirm the formation of nanoflakes of MoS2 and the interface between nanoflakes and polyacrylamide. The band structure was observed from the Raman spectra, which shows the E12g peak at 384.802 cm −1 and 410.039 cm −1 in MoS2 –polyacrylamide. X-ray diffraction (XRD) pattern revealed the crystallinity of the as-prepared metallopolymer, and Fourier-transform infrared (FTIR) spectroscopy confirmed the presence of surface functional groups attached to the metallopolymer. UV-visible spectra of the metallopolymer nanomaterial exhibited the broad range absorption of the spectrum by the metallopolymer. The thermal properties of functionalized metallopolymers were investigated using thermogravimetric (TG) analysis – and differential thermal analysis (DTA). Photodetection was successfully performed via the development of metallopolymer photodetectors. Current–voltage ( I – V ) and time-dependent photoresponse characteristics of MoS2 –polyacrylamide were studied under constant exposure to UV light. The as-prepared metallopolymeric nanomaterial shows enhanced photodetection performance under ambient conditions. The responsivity and detectivity were found to be 60.092 mA W −1 and 4.963 × 10 11 Jones. The rise and the decay time were 0.773 s and 0.386 s with an LDR of 60.092 dB at a very low power of 40 μW cm −2 .